A Limit Theorem on the Core of an Economy with Individual Risks - Caspi, Yaffa Machnes (Review of Economic Studies, 1978)
Journal Article A Limit Theorem on the Core of an Economy with Individual Risks Get access Yaffa Machnes Caspi Yaffa Machnes Caspi The Hebrew University of Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 267–271, https://doi.org/10.2307/2297341 Published: 01 June 1978 Article history Received: 01 July 1976 Accepted: 01 May 1977 Published: 01 June 1978